2022
DOI: 10.1021/jacs.1c11887
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening of Rattling-Induced Ultralow Lattice Thermal Conductivity in Semiconductors

Abstract: Thermoelectric (TE) materials with rattling model show ultralow lattice thermal conductivity for high-efficient energy conversion between heat and electricity. In this work, by analysis of the key spirit of the rattling model, we propose an efficient empirical descriptor to realize the high-throughput screening of ultralow thermal conductivity in a series of semiconductors. This descriptor extracts the structural information of rattling atoms whose bond lengths with all the nearest neighboring atoms are larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 87 publications
0
26
0
Order By: Relevance
“…[1] The k lat being the only independent parameter in the zT equation, discovering new materials having intrinsically low k lat is imperative to achieve high thermoelectric performance. [8][9][10] Several fascinating chemical and physical phenomenon of materials such as strong lattice anharmonicity [11][12][13] , rattling of atoms, [14][15][16][17][18][19] cation-anion disordering [20] off centering atom, [21][22][23] presence of liquid-like sublattices, [24,25] metavalent bonding [26,27] and ferroelectric instability [28] are found to play a vital role for obtaining intrinsically low k lat . To explore new materials with low k lat , a detailed understanding of the relationship among the crystal structure, chemical bonding, and lattice dynamics is essential.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The k lat being the only independent parameter in the zT equation, discovering new materials having intrinsically low k lat is imperative to achieve high thermoelectric performance. [8][9][10] Several fascinating chemical and physical phenomenon of materials such as strong lattice anharmonicity [11][12][13] , rattling of atoms, [14][15][16][17][18][19] cation-anion disordering [20] off centering atom, [21][22][23] presence of liquid-like sublattices, [24,25] metavalent bonding [26,27] and ferroelectric instability [28] are found to play a vital role for obtaining intrinsically low k lat . To explore new materials with low k lat , a detailed understanding of the relationship among the crystal structure, chemical bonding, and lattice dynamics is essential.…”
Section: Introductionmentioning
confidence: 99%
“…LCB crystallized in monoclinic space group C2 with unit cell parameters of a = 11.043 Å, b = 6.563 Å, c = 9.129 Å, β = 91.47°, and Z = 2. 27 As shown in Figure 2a, the basis structural unit of the LCB crystal is the (B 5 O 12 ) 9− double-ring pentaborate group, which is built from two triangular (BO 3 ) 3− units and three tetrahedral (BO 4 ) 5 All of the infinite two-dimensional (2D) planes are superimposed with each other along the c direction to form a three-dimensional structure. When Gd 3+ was introduced, it could occupy the La 3+ or Ca 2+ site simultaneously with partial disorder.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The physical interaction between electron states and lattice vibrations, namely, electron–phonon coupling, is the cornerstone of many intriguing phenomena comprising superconductivity, Jahn–Teller distortion, charge density waves, etc. Therefore, it is very meaningful to elucidate the electron–phonon coupling dependence on the crystal structure, especially the rare-earth (RE) photofunctional materials. , Photoluminescence is a common method to study electron–phonon coupling because lattice vibrations can greatly modulate the electron transitions, accompanied by phonon creation or annihilation . Consequently, the luminescence wavelength can be regulated by red shift (or blue shift) by phonon creation (or annihilation).…”
Section: Introductionmentioning
confidence: 99%
“…These two kinds of anharmonic vibrations trigger additional scattering between phonons, resulting in low lattice thermal conductivity. 4 (LA) phonon mode and the low-lying optical phonon mode within the range of 0.5−0.7 THz are present (highlighted by black circles). This phenomenon is due to the existence of rattling modes in the material, leading to strong anharmonic vibrations.…”
mentioning
confidence: 99%
“…Recently, vacancy-ordered double perovskites A 2 BX 6 have been gaining attention for thermoelectric energy conversion due to unique structural attributes and ultralow lattice thermal conductivity. Researchers have found that Cs 2 SnI 6 is a good n -type thermoelectric material due to its lattice thermal conductivity of 0.29–0.22 W m –1 K –1 in an air-stable environment . Sajjad et al studied the electron and phonon transport properties of Cs 2 PtI 6 and found that heavy elements can act as phonons to effectively suppress the lattice thermal conductivity (0.15 W m –1 K –1 at room temperature) .…”
mentioning
confidence: 99%